Crystalline silica exposure and air quality perception of residents living around home stone factories - Sakesun Thongtip,; Penprapa Siviroj,; Athavudh Deesomchok,; Anawat Wisetborisut,; Tippawan Prapamontol, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Stone factories containing harmful inhalable crystalline silica that can penetrate deep into the respiratory system causing silicosis. People living around stone factories should be concerned about the risk of dust pollutants. This study aimed to assess the crystalline silica concentrations and air quality perception (AQP) among residents living around home stone factories. Forty samples of PM10 and crystalline silica concentrations were collected from 11 home stone factories and measured following the NIOSH methods 0600 and 7601. A cross- sectional study was carried out into 325 subjects who were interviewed using the AQP and respiratory symptoms questionnaires, and a Geographic Information System technique for distance from stone factories was measured. The average crystalline silica concentrations of all stone factories were higher than the recommendation. Bivariate analyses showed that the subjects’ age, income, occupation, smoking, distances, and number of respiratory symptoms were associated with AQP. Interestingly, those with distance from stone factories lower than 50 m had a poorer AQP than those whose distance from stone factories was more than 100 m (cOR 2.5, 95%CI: 1.3-4.9). An increasing number of respiratory symptoms was associated with a poor quality of air perception (B = 0.752, SE = 0.242) and those which had chest pain, nose irritation and stuffy nose were associated with a poor AQP. All home stone factories produce inhalable dust pollutants. The AQP can be used to link distances from pollutant sources and have a relationship with respiratory symptoms. Periodically monitor dust pollutants exposure, AQP and surveillance of respiratory illness should be done.